Establishing successful binational academic collaborations in minority health research - Mier, Nelda; Piziak, Verónica; Zuñiga, Miguel; Sánchez, Esmeralda; Bocanegra Alonso, Anabel; Acosta González, Rosa I. (2005)
This article describes a continuing, successful binational collaborative effort between researchers from two academic institutions in the United States and Mexico addressing health issues on both sides of the Texas/Mexico border region. Researchers from the Texas A&M University System Health Science Center School of Rural Public Health (SRPH) and the Reynosa-Aztlán Multidisciplinary Academic Unit of Universidad Autónoma de Tamaulipas (UAT) partnered to conduct two research projects in the South Texas/Mexico border region. These binational research projects focus on obesity and diabetes, issues that seriously affect border residents. This article also highlights the challenges that must be addressed to sustain binational collaborative efforts and recommendations for successful partnerships